ANALISIS KINERJA APARATUR DALAM PELAYANAN DI KANTOR BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KABUPATEN KUTAI BARAT - Regina Deasy Marlina (Magister Administrasi Publik FISIP Universitas Mulawarman, 2017)
This article aim to describe and analyze the performance of personnel in the public service in the Office of Financial Management and Asset Kutai Barat. Seerta effort - what efforts are made to improve the performance of the apparatus and then to identify and describe the factors - factors that support and hinder the officials at the Office of Financial Management and Asset Kutai Barat. The analysis used in this research is the data analysis interactive model proposed by Miles, Huberman and Saldana stats in qualitative research, data analysis conducted by three (3) lines of activities occurring simultaneously, namely condensation, data presentation and conclusion/verification. The study concluded that the performance of the apparatus in an effort to improve the service has been good, although not optimal, however the services provided have shown progress, this is due to several things: the ability to use working hours in efektf, the quality of the work produced then the responsiveness of employees is good enough.Keywords: apparatur, performance, service